(untitled) (Journal of Engineering Studies and Research, 2025)
Concrete is a geo-material highly used throughout the world. It is made up of granules, cement, and water. It is a composite material of which aggregates are coated by hydrated cement that plays a binder role. The current production of cement factories is estimated to 4.2 billion of tons a year [1]. Its production results in CO2 emissions. Referring to yearly produced cement quantity, it is obvious that it poses the environmental pollution. A previous study emphasized the possibility of creating composite cement of 75 % clinker, and 25% basalt [2]. Throughout this study, we discovered that the strength of this cement-based concrete is slightly lower than 2 days, but 28 days and 90 days higher than the control concrete composed of the same materials as the current Portland cement.